Progesteronrelaterad diabetes mellitus hos älghund - Wallberg, Annelie (2009)
Diabetes mellitus (DM) is a relatively common endocrine disease in dogs and is more common in certain breeds than others, e.g. Nordic spitz breeds. Within the Swedish and Norwegian Elkhound population, female dogs are almost exclusively affected. The hypothesis in this study is that Swedish- and Norwegian Elkhounds develop DM during the progesterone phase of estrous (diestrous or pregnancy).